Digital Twins in Supply Chain: Catalyzing the change towards Circular Economy - Jensen, Johannes; Panneerselvan, Arunkumar (My University, 2024)
This research explores the role of Digital Twin, a key technology in Industry 4.0, in facilitating the shift towards a circular economy via Supply Chains. It also addresses the potential obstacles that hinder the integration of Digital Twin into the Supply Chain. Data was gathered through a comprehensive literature review and interviews with researchers and company personnel to understand the degree to which Digital Twins are utilized in their organizations, and how it can guide them towards circularity in their supply chains.The study reveals that Digital Twins can enhance circularity in supply chains by extending the product lifespan through real-time monitoring and predictive maintenance, as well as by effectively tracking products returned by customers. However, implementing Digital Twin technology in extensive network like supply chains is challenging due to factors that complicate real-time data collection and time-consuming and costly process of modeling every asset. Therefore, in such large networks, a Digital Model could be a more practical and cost-effective solution.
Keywords: Digital Twin; Supply Chain; Circular Economy; Logistics; Linear Economy